Revista Popular (1859-1863) e Jornal das Famílias (1863-1878): um perfil dos periódicos de Garnier - Miranda, Kátia Rodrigues Mello [UNESP]; Azevedo, Sílvia Maria [UNESP] (My University, 2010)
The purpose of this paper is to show some characteristics and essential information related to the Brazilian periodicals in the 19th century Revista Popular (1859-1862) and Jornal das Famílias (1863-1878), whose owner was the Frenchman Baptiste Louis Garnier. By that time the proliferation of periodicals attracts attention mainly because several of them had ephemeral existence, in opposition to Garnier’s periodicals which as a whole amount to 19 years in circulation. The research on these periodicals becomes relevant since they are well succeeded publications whose study makes possible the widening of the knowledge on social and cultural aspects of a very important period in Brazilian society.

Este periódico possui conceito B2 no Qualis da Capes.

A proposta deste artigo é apresentar algumas características e informações essenciais relativas aos periódicos brasileiros do século XIX Revista Popular (1859-1862) e Jornal das Famílias (1863- 1878), de propriedade do francês Baptiste Louis Garnier. Nesse período, a proliferação de periódicos chama a atenção, principalmente porque vários tinham vida efêmera, ao contrário desses periódicos de Garnier que, juntos, somam 19 anos de circulação. A pesquisa dos periódicos em pauta se faz relevante uma vez que são publicações bem sucedidas cujo estudo permite a ampliação do conhecimento de aspectos sociais e culturais de uma importante época da sociedade brasileira.
Keywords: Revista Popular; Jornal das Famílias; Brazilian press; Cultural and literary activity in periodicals; Revista Popular; Jornal das Famílias; Imprensa brasileira; Periodismo cultural e literário